(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Metabolic syndrome is an emerging health problem among young adults, including college students, and is associated with high mortality and morbidity rates. Physical activity is one of the main factors in preventing this syndrome. Objectives This study aimed to evaluate the influence of physical activity levels on the prevalence of metabolic syndrome in college students. Method and Materials The sample included 95 students from a higher education institution, aged between 18 and 45 years. The IPAQ questionnaire was initially used, followed by assessments of body composition by bioimpedance, in addition to measurements of blood pressure, heart rate and blood glucose. For statistical analysis, associations between metabolic syndrome risk factors and physical activity levels were examined using SPSS software. Result The results indicated that individuals classified as very active had greater lean mass, lower body fat percentage, higher bone mineral density and lower resting heart rate compared to sedentary and irregularly active individuals. Conclusion: We conclude that regular physical activity can reduce the risk of metabolic syndrome and promote better health indicators in college students. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 919-924